Comparative macro-anatomic investigations on the pudendoepigastric vein in akkaraman sheep and angora goat - Emrullah Eken; Sadettin Tıpırdamaz (Eurasian Journal of Veterinary Sciences)
The purpose ol this study was to investigate the pudendoepigastric vein in Akkaraman sheep and Angora goat. In this study, as a material, eight of Akkaraman sheep and eight of Angora goats were used It was seen that the pud e ndo epigastric vein formed by the caudal abdominal vein, caudal epigastric vein and external pudendal vein. It was determined that the pudendal external vein formed by the joining of the ventral scrotal vein, ventral labial (caudal mammarial) vein and caudal superficial epigastric (cranial mammanal) vein. The valves (valvula venosa) were seen towards the pudendoepigastric vein.